Pengaruh Penambahan Daun Nangka (Artocarpus Heterophyllus Lam.) Ke Dalam Ransum Ternak Ruminansia Terhadap Kualitas Fisik Pakan Fermentasi - Andi Vikram Nugraha. P; Amriana Hifizah; Ayu Lestari (Anoa: Journal of Animal Husbandry, 2026)
This study aims to determine the effect of adding jackfruit leaves (Artocarpus heterophyllus Lam.) to ruminant livestock rations on the physical quality of fermented feed. This study was conducted at the Animal Feed Laboratory, Department of Animal Science, Faculty of Science and Technology, Alauddin State Islamic University, Makassar from November to December. The research method used was a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of variations in the addition of jackfruit leaves of P0 (0%), P1 (10%), P2 (15%), and P3 (20%) in the ration. The results showed that the addition of jackfruit leaves had a significant effect (P <0.05) on the physical quality of fermented feed, especially on the parameters of color, aroma and pH, while it had no significant effect (P>0.05) on texture. Fermented feed with the addition of 10% jackfruit leaves showed the best quality with characteristics of yellowish green color, fresh aroma and optimal pH. This study provides an alternative forage that can improve the quality of livestock feed.